STRATEGI MEMBANGUN LEARNING ORGANIZATION (LO DALAM MENINGKATKAN MUTU DAN DAYA SAING LULUSAN (STUDI KASUS DI SEKOLAH MENENGAH ATAS (SMA) NU HASYIM ASY’ARI KUDUS) - Masrukhin, Masrukhin (Pascasarjana IAIN Kudus, 2015)
This research aims to detect and describe watchfulness about strategy builds study organization (learning organization) in increase quality and graduate competitiveness (case study at senior high school (SMA) NU Hasyim Asy’ari Kudus. This research method uses to approach qualitative with case studyresearch kind. Informant election is done according to purposive and snowball technique or snowball sampling so that found satisfied data. This research data collecting technique uses: (1) indepth interview; (2) participant observation; and (3) documentation study. Data validity verification is based in four criterias that is credibility, transferability, dependability, and confirmability. This research data analysis uses SWOT analysis. Research finding result that is: (1) strategy is done in build study organization (learning organization) thatis with involve school committee, headmaster, teacher, official, and student with design human resource development (HRD) effectively pass inservicetraining, (2) quality and graduate competitiveness at SMA NU Hasyim Asy’ari Kudus in general belong in good category, but such necessary give many superiorities as response form from stakeholders. Seen from decreased it society interest in latest yrs, (3) strategy builds study organization (learningorganization) done with do communication passes ceremonies that carried out in order to apple morning, and at other activity interrupts, (4) identificationis done according to together by civitas academic person by using SWOT analysis, so that determinable assorted new strategy relevanter with period development demand. SWOT analysis result found as follows: (1) red letter day change from Friday is changed to be day sunday based on demand users(stakeholders), (2) religious teacher involvement in school promotion to get society belief, (3) NU organization is used according to maximal as base toincrease student total and school quality, (4) opinion existence government wisdom SMK as much as 60% and SMA 40% must be responsived with give curriculum load SMA plus that is alive craft after they pass. (5) Synergy between education foundation executor body Ma’arif with SMA NU Hasyim Asy’ari Kudus, (6) location SMA NU Hasyim Asy’ari that flanked by several SMA and SMK with distance close to one another ± 0.5 km and belong also private must innovate in school superiority, (7) Only one way for student doesn’t has vehicle self difficulty moment go to school. School can develop boarding school system that is garrisoned with given study addition matterand superiority speaks everyday Arabian language and English.